Effects of interstitial carbon on the radiation tolerance of carbon-doped NiFe binary alloys from atomistic simulations. (August 2020) - Ge, Guojia; Chen, Feida; Tang, Xiaobin; Huang, Hai; Lin, Jiwei; Shen, Shangkun; Gao, Jing
Highlights: Enhance radiation tolerance of SP-CSAs via interstitial strengthening. Use cascade simulation and defect-driven method to learn defect evolution. Interstitial carbon inhibits the defect diffusion and suppress cluster formation. Abstract: Atomistic simulations were utilized to investigate the effects of interstitial carbon on the radiation tolerance of carbon-doped NiFe binary alloy (NiFeC). Cascade simulation and defect insertion method were implemented to systematically study the radiation-induced defect generation and clustering mechanisms. Results showed that the interstitial carbon reduced the defect counts during the thermal spike expansion in the ballistic stage. For the final survived defect clusters, the cluster size in NiFeC decreased significantly relative to that in NiFe alloy. The energetic and kinetic calculations verified the migration behavior of the interstitial and vacancy in NiFeC. The mobility of the interstitial was inhibited by the lattice distortion aggravated by interstitial carbon. The vacancy tended to bind with the carbon atoms and remained immobile. Both characteristics suppressed the formation of large-sized clusters, such as dislocation loop and stacking fault tetrahedra observed in NiFe.